Microarray gene expression profiling and bioinformatics analysis reveal key differentially expressed genes in clival and sacral chordoma cell lines. (3rd June 2019) - Li, Gaowei; Cai, Linjun; Zhou, Liangxue
ABSTRACT: Objective : Chordoma is a rare tumor with a certain rate of distant metastasis. Skull base and sacrum are the two most common origin sites. This study tends to identify key differentially expressed genes (DEGs) between classical clival and sacral chordomas, provide new targets for future treatment options of chordomas. Methods : The gene expression profiles of GSE95084 and GSE68497 were downloaded from Gene Expression Omnibus database and were analyzed using the limma R package. Function and enrichment analyses of DEGs were performed based on DAVID Database. Protein–protein interaction (PPI) network was constructed using the Cytoscape based on the data collected from STRING online datasets. Hub genes selection and modules analyses of the PPI network were conducted by plugin cytoHubba and MCODE of Cytoscape software, respectively. Result : In total, 728 genes, including 363 up-regulated genes and 365 down-regulated genes were selected as DEGs. Notably, GO analysis showed that both up-regulated and down-regulated DEGs were mainly involved in cell component such as an integral component of the membrane, plasma membrane and extracellular exosome. DEGs were mainly enriched in pathways like Pathways in cancer, PI3K-Akt signaling pathway, Cytokine-cytokine receptor interaction. FYN, ITGB3, ACTN2 and IGF1 were identified as hub genes and they were all involved in focal adhesion signaling pathway. Furthermore, five significant network modules were obtained from the PPI network. Conclusion : This study helps to further understand the molecular characteristics of classic chordomas of two distinct sites. Hub genes FYN, ITGB3, ACTN2, and IGF1, as well as focal adhesion signaling pathway, would be new targets for future treatment options of chordomas.